2020
DOI: 10.1177/0734016820966038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Muslim Religiosity on Youth Delinquency

Abstract: Conceptualizing religiosity as a multidimensional construct, this study aimed to investigate the influence of religiosity on youth delinquency. Three dimensions of religiosity—belief about religion, religious practice, and religious social environment—were examined as predictors of delinquency. The survey data collected in 2010 by the Governance of Istanbul, Istanbul Department of Education, and Istanbul Police Department were used. Participants were high school students ( n = 31,272) between 14 and 18 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 84 publications
(124 reference statements)
2
6
0
Order By: Relevance
“…An overlap between religious and secular moralities implies that religion would not override the deterrent effect of secular morals on deviance but may have value added effect for deterrence. This contention is consistent with the previous findings of religious influence on both ascetic and secular deviance (Cochran 1988;Harris 2003;Jang 2018) as well as null findings on the impact of religion on some but not all forms of deviance (Abu-Rayya et al 2016;Baier and Wright 2001;Groves, Newman, and Corrado 1987;Helal and Coston 1991;Ozbay 2007Ozbay , 2015Sahin and Unlu 2021;Souryal 1987;Stark 2001). 2 Thus, our argument is that despite 2 This is likely a byproduct of social context, in which the role of (a still salient) religion varies from place to place.…”
Section: Secularization Religion and Deviancesupporting
confidence: 92%
See 2 more Smart Citations
“…An overlap between religious and secular moralities implies that religion would not override the deterrent effect of secular morals on deviance but may have value added effect for deterrence. This contention is consistent with the previous findings of religious influence on both ascetic and secular deviance (Cochran 1988;Harris 2003;Jang 2018) as well as null findings on the impact of religion on some but not all forms of deviance (Abu-Rayya et al 2016;Baier and Wright 2001;Groves, Newman, and Corrado 1987;Helal and Coston 1991;Ozbay 2007Ozbay , 2015Sahin and Unlu 2021;Souryal 1987;Stark 2001). 2 Thus, our argument is that despite 2 This is likely a byproduct of social context, in which the role of (a still salient) religion varies from place to place.…”
Section: Secularization Religion and Deviancesupporting
confidence: 92%
“…Although the relationship between Christianity and deviance has been examined in western criminology since the 1960s (Baier and Wright 2001;Middleton and Putney 1962;Miller and Vuolo 2018), a gap remains in our understanding of the relationship between Islam and deviance because of limited research in non-western societies. Previous studies on that subject, though small in number, have found Islam's influence on deviance was not significant or, at best, weak (Abu-Rayya et al 2016;Groves, Newman, and Corrado 1987;Helal and Coston 1991;Junger and Polder 1993;Ozbay 2007Ozbay , 2015Sahin and Unlu 2021;Serajzadeh 2002;Souryal 1987;Stark 2001).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Still, given that no studies have truly used the Islamic concepts of religiosity, for example as denoted by Desouky & Umarji (2021), the true extent to which Muslim religiosity, with its different elements, affects the levels of delinquency is currently unknown. This is especially noteworthy when Sahin's (2021) study provided early evidence that different elements of Muslim religiosity have different relationships with delinquency. Currently, the majority of the literature has only offered insight into the influence of Muslim religiosity through the perspective of general religiosity (using the properties of Muslim religiosity that are shared with other faiths such as abstinence, religious attendance, and the role of the religious institutions).…”
Section: Discussionmentioning
confidence: 99%
“…Item 6, 7, 9, 10, 11, and 13 were omitted from the final scoring importance of abstinence and its interplay with the status of religiosity (Carol et al, 2020). Lastly, out of the 15 articles, only three studies used a measure that was specifically developed to conceptualize Muslim religiosity (Demmrich & Akgül, 2020;French et al, 2008;Sahin & Unlu, 2021). Demmrich and Akgül (2020) adopted a scale of religiosity for Muslim Turkish adolescents that was developed by Horozcu & Demir (2018) by considering different aspects of the Islamic belief such as the Holy Book and the Prophet.…”
Section: Operationalization Problems Of Muslim Religiositymentioning
confidence: 99%